The language of spirituality - Gellel, Adrian-Mario (2018)
By exploring the evidence brought forward by palaeontologists and archaeologists, this paper will investigate the hypothesis that spirituality is rooted in our primordial origins. It will be claimed that as a fundamental human dimension that distinguishes humans, spirituality needs to interact with the other constituent dimensions that make us human, including our need for community, our characteristics of learning, of being rational and of developing tools that change us. If spirituality emerged so early in the evolutionary process, and if it is tied to the quest of search for meaning, one could put forward an argument that it precedes most of the tools and knowledges developed by humans. There seems to be evidence that its ability to spur human development is mainly done through the development and use of symbols which, if understood in a wider sense, seem to be the primary language of spirituality.
Keywords: Spirituality; primordial spirituality; symbol literacy; Symbols